Barriers to using market intelligence in plant breeding: Evidence from a survey of breeding professionals - Rice, Brendan; Kramer, Berber; Trachtman, Carly (CGIAR, 2024)
Using market intelligence to inform breeding investment decisions is critical in matching the supply of genetic innovations with existing demand and prioritizing market segments where there is the greatest potential for delivering impact. This brief draws from a survey of more than 500 breeding professionals to identify characteristics of current market intelligence use in breeding and the barriers to greater use in breeding decisions. We find that while market intelligence appears to have a foothold in breeding teams, the use of market intelligence is still primarily done in an ad hoc manner, and participation of disciplines needed to effectively generate and integrate market intelligence is lacking. Promoting the use of market intelligence in breeding decisions will not only require increasing the availability of quality information but also supporting breeding teams in translating that market intelligence information into varietal advancement and pipeline investment decisions. Moreover, adverse attitudes and misaligned incentives may be inhibiting the use of market intelligence. Specifically, we find that breeding team attitudes on who should be involved in breeding programs may be limiting the move to more transdisciplinary approaches and that current institutional incentive structures may not incentivize the use of market intelligence in breeding decisions. Finally, we discuss ways forward in scaling the more systematic use of market intelligence in breeding decision-making.